The velocity of unloaded shortening and its relation to sarcomere length and isometric force in vertebrate muscle fibres. - Edman, K A (1979)
1. The velocity of shortening at zero load was studied during fused tetanic contractions and single twitches in isolated skeletal muscle fibres of Rana temporaria. 2. The technique used for determination of the speed of unloaded shortening consisted of a series of quick releases of different amplitudes applied at a given instant during activity. The time, delta t, needed for the fibre to take up the slack was plotted against the amplitude of release, delta L. The slope of the straight line relating delta t-delta L provided a measure of the velocity of shortening at zero load, V0. 3. V0 was compared with force-velocity data obtained at finite loads (load-clamp recordings). The predicted velocity of shortening at zero load, derived by hyperbolic extrapolation from velocities at low and intermediate loads, was not significantly different from V0. 4. The temperature dependence of isometric force and of shortening velocity was investigated between 2 and 12 degrees C in the same fibres. Q10 was 2.67 +/- 0.07 (S.E. of mean, n = 6) for V0 and 1.24 +/- 0.01 for tetanic force. 5. The velocity of unloaded shortening was determined at different sarcomere lengths in the range 1.4--3.1 microns. V0 was constant between 1.65 microns and approximately 2.7 microns. It decreased below 1.65 microns and increased above 2.7 microns. 6. The decrease in velocity at short sarcomere lengths probably reflects an increase of the passive resistance to shortening. The increase in velocity at long sarcomere lengths can be accounted for by the passive compressive force that is produced by the parallel elastic elements of the prestretched fibre. 7. V0 was determined at the peak of the twitch and during the plateau of the fused tetanus in the same fibre. Whereas the peak twitch force varied between 38 and 85% of the tetanic tension in the different fibres (mean: 71 +/- 5%, n = 8), V0 during the twitch was 99 +/- 2% of the value recorded during the tetanus. Depression of the isometric twitch amplitude to 10% of the control value by dantrolene did not cause any significant reduction of V0.